Agama dan Tradisi Lokal Banten: Studi Ritualitas Panjang Mulud di Serang Banten - Al Ayubi, Sholahuddin (TAJDID, 2017)
The characteristics possessed by local society in developing tradisi mawludan (the birthday of the Prophet Muhammad) is involved in lengthy cultural process. Etymologically, mawludan means birthday, but such this tradition has been developing variously in some particular places. Consequently, celebrating mawludan tradition in Banten is possessed of values, norms, particular symbols, and this tradition is even held with adapting to the modern life. In the regions of Banten, celebrating mawludan can't get rid of motivations, religion norms, and behaviorism. This ritualistic mawludan tradition has been developing offering, performance, and the customs in different way. In addition, celebrating this ritualistic tradition has particular norm and ethics. This writing, as a result of study tries to illustrate how the ritualistic panjang mawlud is held in Serang and how to be connected with religion.